The protective effects of melatonin and vitamin E on antioxidant enzyme activities and epididymal sperm characteristics of homocysteine treated male rats - Sönmez, M; Yüce, A; Türk, G (My University, 2007)
The aims of this study were to investigate the effects of homocysteine (Hcy) on epididymal sperm characteristics, plasma testosterone level and biochemical changes related to oxidative stress and to examine the effects of melatonin (Mlt) or Vitamin E (VE) administration on these parameters in Hcy-treated male rats. In this study, 32 adult male albino rats of Wistar strain were used. The rats were randomly divided into four groups. The first group of rats received only Hcy (0.71 mg/kg/day) intraperitonially (ip) for 6 weeks. The second group of rats was given Hcy along with simultaneous administration of Mlt (1 mg/kg/day) subcutaneously. The third group of rats received Hcy along with simultaneous administration of VE (125 mg/kg/day, ip). The fourth group of rats served as control during 6 weeks and was daily given 0.1mL of physiological saline (NaCl, 0.9%) ip. While the plasma malondialdehyde level significantly (p < 0.05) increased, the plasma superoxide dismutase, glutathione peroxidase and catalase activities significantly (p < 0.05) decreased in Hcy-treated rats when compared to control rats. Furthermore, the epididymal sperm concentration, the percentage of progressive sperm motility and plasma testosterone level were significantly (p < 0.05) lower in Hcy-treated rats than those of the control rats. The simultaneous administration of Mlt or VE to Hcy-treated animals impeded the decrease in the plasma antioxidant enzyme activities, testosterone level, the epididymal sperm concentration and motility. In conclusion, this study indicates that chronic administration of Hcy has the harmful effect on the epididymal sperm characteristics of male rats. The administration of Mlt or VE can prevent adverse effects of Hcy on the plasma antioxidant enzyme activities, testosterone level, epididymal sperm count and motility in male rats.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Homocysteine Sperm Melatonin Vitamin E Lipid peroxidation Rat